High-Performance and Specialty Fibers Concepts, Technology and Modern Applications of Man-Made Fibers for the Future - The Society of Fiber Science and Techno, Japan; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2016)
This book reviews the key technologies and characteristics of the modern man-made specialty fibers mainly developed in Japan. Since the production of many low-cost man-made fibers shifted to China and other Asian countries, Japanese companies have focused on production of high-quality, high-performance super fibers as well as highly functionalized fibers so-called 'Shin-gosen'. ZylonTM and DyneemaTM manufactured by Toyobo, TechnoraTM produced by Teijin, and VectranTM developed by Kuraray are those examples of super fibers. Carbon fibers ToraycaTM from Toray have occupied the most advanced high-performance application area. Various types of polyester fibers having design-shaped cross-sections and special fiber morphologies and those showing specific physico-chemical properties have also been developed to acquire a high-value textile market of the world. This book describes how these high-techfibers have been developed and what aspects are the most important in each fiber based on its structure-property relationship. Famous specialists both in industry and academia are responsible for the contents, explaining the design concepts and the special technologies for the production of these special fibers. For university teachers and students, this volume is an excellent textbook that elucidates the basic concepts of modern fibers. At the same time, researchers, both in academia and industry, will find a comprehensive overview of recent man-made fibers. This publication, presenting the most easily understandable general survey of specialty man-made fibers to date, is dedicated to the 70th-anniversary of the Society of Fiber Science and Technology, Japan.
History of Fiber Structure -- Progress in Structure Analysis Techniques of Fibers -- Progress in Fiber Spinning Technology -- History of Polyester Resin Development for Synthetic Fibers and Its Forefront -- History of Super Fibers: Adventures in Quest of the Strongest Fiber -- Microscopically-Viewed Relationship between Structure and Mechanical Property of Crystalline Polymers: An Important Guiding Principle for the Development of Super Fibers -- Dyneema(R): Super Fiber Produced by the Gel-Spinning of a Flexible Polymer -- Development of High-Strength Poly(ethylene terephthalate) Fibers: An Attempt from Semi-flexible Chain Polymer -- Technora(R) Fiber: Super Fiber from the Isotropic Solution of Rigid-Rod Polymer -- Vectran®: Super Fiber from the Thermotropic Crystals of Rigid-Rod Polymer -- Zylon®: Super Fiber from Lyotropic Liquid Crystal of the Most Rigid Polymer -- Overview of Functional and Speciality Fibers -- High-Touch Fibers and "Shin-Gosen" -- Moisture and Water Control Man-Made Fibers -- Heat-Controllable Man-Made Fibers -- Nanofibers -- Nanofiber by Conjugated Spinning -- Cellulose Nanofibers as New Bio-Based Nanomaterials -- Forefront of Nanofibers: High Strength Fibers and Optoelectronic Applications -- Carbon Fiber -- Pitch Based Carbon fibers -- Life Cycle Assessment of Carbon Fiber Reinforced Plastic -- Recycling Technologies of Carbon Fiber Composite Materials -- Current Status and Future Outlook for Nonwovens in Japan -- Bicomponent Polyester Fibers for Nonwovens -- The World's Only Cellulosic Continuous Filament Nonwoven "Bemliese" -- Thermoplastic Polyurethane Nonwoven Fabric "Espansione" -- Future Man-Made Fiber.
Keywords: Ceramic materials; Polymers; Manufactures; Ceramics; Polymers; Machines, Tools, Processes